Keseimbangan Tanggung Jawab KBM FH Dalam Mencapai Prestasi Akademik dan Non-Akademik Di Bidang Organisasi Atau Kepanitiaan Ditinjau Dari Aspek Kepemimpinan - Cantika Tresna Rahayu; Chelsea Kairadinda Adam; Firda Amalia; Syahirah Rafah Santika; Dwi Desi Yayi Tarina (Student Research Journal, 2024)
Higher education is an important foundation for individual and societal development. However, students often face challenges in maintaining a balance between academic demands and active participation in non-academic activities, such as organizations and committees. This research aims to explore the dynamics of Law Faculty (FH) students' responsibilities in Teaching and Learning Activities (KBM) and their roles in organizations and committees, with an emphasis on leadership aspects. This research uses a quantitative descriptive approach, by collecting data through questionnaires distributed to 32 FH students who are active in student organizations. The research results show that the majority of respondents are able to divide their time between academic and non-academic activities well. Most respondents prioritize academic activities when facing exams, but remain consistent in organizational responsibilities. These findings emphasize the importance of balance between academic and non-academic activities in achieving optimal achievement at FH. In addition, the role of leadership is considered crucial in helping students manage their responsibilities effectively. It is hoped that this research can make a significant contribution to the development of higher education and student leadership at the Faculty of Law.